Unruptured anterior Inferior cerebellar artery aneurysm following stereotactic irradiation for vestibular schwannoma: Case report and literature review - Lu, Denghui; Ping, Haoda; Wei, Chen; Fang, Wei; Zhang, Yunze; Wu, Yingxi; Xue, Yafei; Wang, Bao; Qu, Yan; Zhao, Tianzhi (Frontiers in Surgery, 2023)
Background: The clinical features and therapeutic measures of vestibular schwannoma radiation-related aneurysm have not been well described. We reported the first vestibular schwannoma radiation-related aneurysm case admitted for acute anterior inferior cerebella artery ischemic symptoms. Literature was reviewed to present the research fruits about vestibular schwannoma radiation-related aneurysms, and some therapeutic advices were given. Materials and methods: A 54-year-old woman who had undergone GKS 10 years previously for a right VS was admitted to our hospital in 2018 because of sudden onset of severe vertigo and vomiting, accompanied with unsteady gait. During tumor resection, a dissecting aneurysm arose from the main trunk of AICA was encountered accidently within the tumor. The aneurysm was successfully treated with direct clip ligation, sparing the parent vessel. Data about this case were combined with those of other 11 radiation-related anterior inferior cerebella artery aneurysm cases retrieved from the current literature. The following parameters were evaluated: Age, Sex, Diagnostic method, Location of aneurysm, Age of radiotherapy (Years)/Latency, Rupture, X-ray dosage, Type of radiotherapy, History of surgical resection of vestibular schwannoma, Aneurysm Type, Morphology, Number, Treatment, Operative complications, Sequela, Outcome. Vestibular schwannoma radiation-related aneurysms mainly occurred in women (75%) with a median age of 62.5 years and were mainly located on anterior inferior cerebella artery. Ruptured aneurysms accounted for 75.0% of the total cases. This paper reported the first vestibular schwannoma case admitted with acute anterior inferior cerebella artery ischemic symptoms. Cases with sacciform-like, irregular and fusiform-shaped aneurysms accounted for 50.0%, 25.0% and 25.0% of the total, respectively. After surgical treatment, 75.0% patients recovered, except for 3 patients who developed new ischemic consequence. Conclusion: Patients should be informed of the risk of radiation-related aneurysms after receiving radiotherapy for vestibular schwannoma. In these patients, radiation-related aneurysms should be suspected when subarachnoid hemorrhage or anterior inferior cerebella artery ischemic symptoms occurred. Active intervention should be conducted considering the high instability and bleeding rate of vestibular schwannoma radiation-related aneurysms.